Residências em saúde: processo ensino-aprendizagem no contexto da Covid-19 - Barreto, Giani dos Santos Alves (2023)
Introduction: Teaching-service integration aims to strengthen professional training in residency courses in health and contribute to changes in professional performance and management, in line with the principles and guidelines of the Unified Health System. Objectives: To analyze the teaching-service process learning in the Integrated Multiprofessional Residency Programs in Family Health and Family and Community Medicine of the State Foundation for Family Health in partnership with the Oswaldo Cruz Foundation, through the eyes of professors, in the context of the Covid-19 pandemic. Methodology: This is a descriptive-exploratory research, with a qualitative approach, whose research participants were the teachers of the Integrated Residency Programs. The field of study was in 04 Family Health Units in the city of Salvador-Bahia. The data collection technique was a semi-structured interview, consisting of 11 professors. Data analysis was performed through the analysis of similarity and word clouds using the IRAMUTEQ software and Bardin's Content Analysis technique. Results and Discussion: After reading and careful analysis of the data, the characterization of the study participants was identified and the categories were apprehended: understanding of the teachers' practice and discussion of the facilities and difficulties of the training process, in the context of the Covid-19 pandemic. The study indicates that innovations were necessary to maintain teaching activities, within the scope of the residents' training process, during the pandemic. Among them, the suspension of face-to-face theoretical activities, which began to take place remotely, and the maintenance of practical activities for residents. The difficulties faced were the lack of knowledge about the disease, the suspension of face-to-face theoretical classes, readjustment to remote classes, fear, insecurity, isolation and social distancing. As a final product, a practical-pedagogical guide was developed with guidance on pedagogical practices in Integrated Residency Programs, in the context of the Covid-19 pandemic. Final Considerations: The performance of teaching practice during the training of residents has undergone changes in planning and execution with regard to the reorganization of the work process. The research aims to contribute to enrich the theme and improve the residents' teaching-learning process, in addition to providing subsidies for discussions and future studies about the impacts caused in crisis situations in the training process.